MUSEUMS IN KYIV (1830'S - 1919): FORMATION, DEVELOPMENT, TRANSFORMATION DURING THE REVOLUTION (City: History, Culture, Society, 2020)
The article analyzes the formation and development of Kyiv museums during the imperial period, as well as the transformations, that took place in this field during the revolutionary period (1917 - 1919). The article deals with the history of museums through the prism of analyzing the contribution of central and local authorities to the development and further activities of museum institutions. The influence of the state authorities and the Ukrainian national movement on the development of museums is considered in the example of the largest Kyiv museums.  Museums have played an essential role in the formation of collective memory, memory policy, the nation-building processes et cetera. During the study period in European countries, national museums were opened. As P. Aronsson and G. Elgenius mentioned, «The national museum is thus a knowledge-based socio-political institution, with corresponding collections and displays that ultimately claim, articulate and represent dominant national values and myths». This article examines the potential of Kyiv museum institutions to become Ukrainian national museums.Kyiv during the imperial period was an important centre of Russian culture and power. For imperial authorities, Kyiv was the administrative centre of the Southwestern region, the city from which Christianity spread, the centre of Russification of Ukrainian territory et cetera. At the same time, Kyiv was the centre of the Ukrainian movement in the Russian Empire. The Ukrainian activists could perceive this city in a completely different way – as a historic capital. For the Ukrainian intelligentsia of the Russian Empire, museum institutions had great potential in the study of the history and culture of Ukrainian lands.The first museums in Kyiv were opened at St. Volodymyr University in the 1830s. The most significant museums in the city were the Church-Archeological Museum at the Kyiv Theological Academy and the Kyiv City (Art, Industrial and Scientific) MuseumThere was no purposeful state museum policy in the Russian Empire. At the same time, the imperial and local authorities had an influence on the creation of museum institutions and their further development (mostly through funding). From the point of view of imperial power, which acted in a particular paradigm of non-recognition of Ukrainians as a separate people, Kyiv museums were supposed to be “Russian”, followed by, or should be followed by, authorities of all levels. However, supporters of the Ukrainian national movement, occupying official positions, used the museums for their purposes, finding opportunities to involve local authorities and patrons. The city's museums operated under different signage, but they had the potential to become Ukrainian national museums, most of all the Kyiv City Museum. This museum has evolved accordingly, thanks to scholars associated with it.In 1917 - 1919 the situation in the city changed. Ukrainian state entities - the UNR and the Ukrainian state, of course, had completely different views on the development of the Ukrainian nation and sought to implement the "Ukrainian project" by creating their state. History and culture were now an essential lever of legitimizing the new government, which, thanks to the influence of the Ukrainian intelligentsia, understood the possibilities of the museum industry. The Ukrainian National Museum had a crucial role in this process. There was no doubt that it should be based in Kyiv, the capital of Ukraine.
Keywords: museums; national museum; Ukrainian national movement; state authorities